Kepemimpinan Transformasional Kepala Sekolah di SMP Muhammadiyah Semin - Yuliana, Rohmah; Sulisworo, Dwi; Hasanah, Enung (Academy of Education Journal, 2025)
Principal transformational leadership in the era of technology and tight competition between schools provides new challenges and opportunities in developing school quality. This study aims to determine the implementation of transformational leadership at SMP Muhammadiyah Semin which has 30 teachers, and a principal who is always innovative and creative in developing and improving school quality. The principal of SMP Muhammadiyah Semin is able to deliver and change the public image of the school which initially began to decline in quality and public trust into a school that is the main destination for prospective students from various sub-districts. This study uses a descriptive qualitative approach with data collection techniques using in-depth interviews with the principal. Currently, the implementation of transformational leadership at SMP Muhammadiyah Semin can improve according to the vision and plan prepared by the management team. In its implementation, the principal gets problems and challenges from within and outside the school. These problems come from teachers, school facilities, and government policies related to PPPTK and DPK teachers. However, the principal can find a strategy from the challenges faced so that the leadership at SMP Muhammadiyah Semin can develop even better.